Constitutional Amendments: Making, Breaking and Changing Constitutions (2019). Oxford: Oxford University Press, 338 pages, ISBN 9780190640484 - Bisariyadi, Bisariyadi (Universitas Negeri Semarang, 2020)
When a constitutional judge willing to spend his time to give a review to a book, it is a great sign that the book has some appeals to offer. Yet, the book that is currently will be reviewed is not only discussed by one but two constitutional judges. At the end of November 2019, two constitutional judges, Saldi Isra and I Dewa Gede Palguna, discussed a book entitled â€œConstitutional Amendment: Making, Breaking and Changing Constitutionsâ€ written by Richard Albert. The attention to the book did not only appear in Indonesia. In the authorâ€™s origin, North America, the book received great acknowledgment from a wide range of legal and political scholars whom people often used to reference their works. Distinguished names like Bruce Ackerman, Tom Ginsburg, Ran Hirschl, Vicki Jackson and Mark Tushnet, encourage audiences to have a close examination of this recent Richard Albertâ€™s publication. Richard Albert, himself, is not a foreign name to political science communities, as well as constitutional law academics. Albert is one of the founders and editors of the International Journal of Constitutional Law (ICON). The book offers two distinct novelty as its strength. First, the book raised a very important issue in the constitutional discourse but rarely been discussed. the second strength of Albertâ€™s works is his mastery in capturing the constitutional amendment process in many countries around the globe and mapping them as well as structuring their similarities.